Strategi Komunikasi Pemasaran Fit Center Club TM dalam Mempertahankan Loyalitas Pelanggan - Syamaidzar Agusetyawan; Agustrijanto (UNIVERSITAS KALBIS, 2022)
Marketing communication strategies have an important role in maintaining customer loyalty, including for Fit Center Club TM as an authorized Herbalife distributor and weight management facility that faces the challenges to maintain good coach-customer relationships, as well as maintain customer loyalty. This study aims to determine the marketing communication strategy implemented by Fit Center Club TM in maintaining customer loyalty. This study uses descriptive qualitative methods and data collection techniques through observation, semi-structured interviews, and documentation of coaches and customers at the Fit Center Club TM as resource persons. The results show that Fit Center Club TM uses a personal selling marketing communication strategy that is integrated with the marketing communication mix such as sales promotions in maintaining good relationships and maintaining customer loyalty properly and effectively which keeps customers loyal and comfortable with the services provided during routine programs and non-routine activities.